1968
DOI: 10.1002/app.1968.070120115
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole catalysis in the curing of epoxy resins

Abstract: SynopsisThe high catalytic activity of imidazoles and particularly of 2-ethyl-4-methylimidazole (EMI) for the curing of epoxy resins and the properties of the resulting resins prompted this study concerned with the nature of the curing reaction. Epon 828 epoxy resin and the model compound phenyl glycidyl ether were used BS starting materials with EMI, 2-methylimidazole, and dimethylbenzylamine as catalysts. During the curing of the resin at 50°C., the decrease in the infrared absorption of the epoxy band with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
3
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 1 publication
1
83
3
2
Order By: Relevance
“…[1][2][3] In this work, as shown in Figure 4, each curve analyzed is typically parabolic, which is also indicative of an autocatalytic kinetics of the studied DGEBA/EMI-2,4 system. 9 For the thermosetting resins that follow autocatalytic kinetics, the expression of f ðÞ, which excludes diffusion-controlled, fusion, and inversion-type reactions, is:…”
Section: Theoretical Analysismentioning
confidence: 54%
See 3 more Smart Citations
“…[1][2][3] In this work, as shown in Figure 4, each curve analyzed is typically parabolic, which is also indicative of an autocatalytic kinetics of the studied DGEBA/EMI-2,4 system. 9 For the thermosetting resins that follow autocatalytic kinetics, the expression of f ðÞ, which excludes diffusion-controlled, fusion, and inversion-type reactions, is:…”
Section: Theoretical Analysismentioning
confidence: 54%
“…[1][2][3] The adducts were believed to be the catalyst that initiated the etherification reactions which cross-link the epoxy resins and determine the final properties of the network. Previous work 5 showed that the formation of adduct was necessary prior to the etherification reaction.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from DBU and DABCO, imidazoles have been widely used for curing epoxy resins as cured epoxy resins give good thermal resistance and physical properties because of the reactivity in chain polymerization with epoxide [12,13]. Latent thermal initiators of imidazoles have been developed.…”
Section: Introductionmentioning
confidence: 99%